Long‐Lived Multifunctional Superhydrophobic Heterostructure Via Molecular Self‐Supply. Issue 5 (28th December 2015) - Huang, Yongfeng; Hu, Ying; Zhu, Chongqin; Zhang, Fan; Li, Hui; Lu, Xinghua; Meng, Sheng
Abstract : Superhydrophobic (SHO) surfaces have drawn great attention thanks to their theoretical significance and myriad applications in industry and everyday life. Current approaches to fabricate such surfaces require calcinating at high temperatures, tedious and time‐consuming treatments, toxic chemicals, and/or processing with intricate instruments. Long‐duration SHO surfaces are even more challenging due to material instability and easy contamination by organic pollutants in dry conditions. To overcome these difficulties we design a simple approach via self‐supplying of low surface tension chemicals to nanoparticles to fabricate multifunctional SHO heterostructures. The method herein features room temperature, rapid processing, with environment‐friendly raw materials. With multiple functions such as photocatalysis and transparency SHO surfaces further extend their lifetime and enable self‐sustaining environment maintenance. Abstract : Multifunctional superhydrophobic (SHO) heterosctructures are fabricated by a simple approach using a self‐supply of low surface tension chemicals to nanoparticles. The method is carried out at room temperature, with rapid processing and environmently‐friendly raw materials. With multiple functions such as photocatalysis and transparency, SHO surfaces further extend their lifetime and enable self‐sustaining environment maintenance.